Transcriptional Profiling of Rice Treated with MoHrip1 Reveal the Function of Protein Elicitor in Enhancement of Disease Resistance and Plant Growth - Lv, Shun; Wang, Zhenzhen; Yang, Xiufen; Guo, Lihua; Qiu, Dewen; Zeng, Hongmei (Frontiers in Plant Science, 2016)
MoHrip1 is a protein elicitor isolated from Magnaporthe oryzae and was found to induce blast-resistance in rice. To investigate the comprehensive functions of MoHrip1, next-generation sequencing (NGS)-based digital gene expression (DGE) profiling was performed to collect the transcriptional data of differentially expressed genes induced by MoHrip1. A total of 308 genes were identified with differential expression, and 80 genes were predicted to be induced specifically by MoHrip1. Among these 308 genes, a series of genes associated with the salicylic acid (SA) pathway, phytoalexin, transcription factors and pathogen-related proteins were identified. Both the SA signaling pathway and the gibberellin (GA) pathway were activated, while the jasmonic acid (JA) signaling pathway was repressed. The contents of endogenous SA and GA and the morphological characteristics of the rice after treatment were measured to provide evidence supporting the predictions made based on the DGE data. The 80 genes mentioned above might be candidate genes for studying interactions with MoHrip1. The transcriptional data provided global effect information in rice induced by MoHrip1, and all the results demonstrated that MoHrip1 could induce pathogen resistance and promote plant growth by regulating the contents of SA and GA directly or indirectly.